2010
DOI: 10.3892/ijo_00000629
|View full text |Cite
|
Sign up to set email alerts
|

Specific mitochondrial calcium overload induces mitochondrial fission in prostate cancer cells

Abstract: Abstract. Mitochondria are structurally complex organelles that undergo fragmentation or fission in apoptotic cells. Mitochondrial fission requires the cytoplasmic dynamin-related protein, Drp1, which translocates to the mitochondria during apoptosis and interacts with the mitochondrial protein, Fis1. Finely tuned changes in cellular calcium modulate a variety of intracellular functions; in resting cells, the level of mitochondrial calcium is low, while it is higher during apoptosis. Mitochondria take up Ca 2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 31 publications
4
8
0
Order By: Relevance
“…Similar results were observed before in differentiated human thyroid cells (Manole et al 2001). In addition, overexpression of cyclin D1 was detected in several papillary thyroid carcinomas (Lazzereschi et al 1998, Shi et al 2001, Khoo et al 2002, Kumar et al 2010.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results were observed before in differentiated human thyroid cells (Manole et al 2001). In addition, overexpression of cyclin D1 was detected in several papillary thyroid carcinomas (Lazzereschi et al 1998, Shi et al 2001, Khoo et al 2002, Kumar et al 2010.…”
Section: Discussionsupporting
confidence: 75%
“…Benign and malignant thyroid cells and tissues express functional oestrogen receptors (ERs) and their growth is stimulated by oestrogen (Furlanetto et al 1999, Manole et al 2001, Ceresini et al 2006, Kumar et al 2010, Rajoria et al 2010, Di Vito et al 2011. In addition, the presence of these receptors has also been demonstrated in thyroid vessels that may be relevant for the vascularization of neoplastic tissues (Ceresini et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These cells express functional ERs and enhance DNA synthesis and proliferation in response to E 2 stimulation. Similar results were obtained in thyroid cells derived from goiter nodules and in human thyroid carcinoma cells (Manole et al 2001, Zeng et al 2007, Kumar et al 2010, Rajoria et al 2010). E 2 -stimulated cell growth was associated with increased expression of cyclin D1 protein, which plays a key role in the regulation of the G1/S transition in the cell cycle (Motokura & Arnold 1993, Manole et al 2001.…”
Section: Effect Of Estrogen On Benign and Malignant Thyroid Cellssupporting
confidence: 76%
“…The strongest support for estrogen as a risk factor of differentiated thyroid cancer comes from experimental studies that have clearly demonstrated that E 2 , the main female sex hormone, is a potent stimulator of both human benign and malignant thyroid cells (Manole et al 2001, Zeng et al 2007, Chen et al 2008, Kumar et al 2010, Rajoria et al 2010. Interestingly, E 2 was equally potent in its growth-promoting effect on human thyroid cells derived from male and female thyroid glands, which underlines the relevance of the hormone rather than of other sex-specific factors (Manole et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Investigations with thyroid cancer cell lines and also some human thyroid tumors have demonstrated the expression of ERs in thyroid tumor cells, both neoplastic and non-neoplastic, indicating that thyroid cells are likely to experience effects of estrogen or ERs (Lee et al 2005, Zeng et al 2007. In fact, the administration of estrogen has been associated with thyroid cell growth and proliferation and also with some changes in other markers of proliferation, growth, and angiogenesis, demonstrating not only the intracellular role of estradiol and ERs, but also their role in the transcription of other genes (Tangjitgamol et al 2005, Zeng et al 2007, Ranks et al 2009, Kavanagh et al 2010, Kumar et al 2010, Rajoria et al 2010, Kamat et al 2011. A recent study has demonstrated crosstalk between ER and PPARg, indicating that levels of expression of ERa (ESR1) and ERb (ESR2) are related to PPARg levels in the cell.…”
Section: Endocrine-related Cancermentioning
confidence: 99%